Headhunting and Colonialism - Roque, R. author. aut Link
XIV, 342 p.
Keywords: An exploration of headhunting and the collection of heads for European museums in the context of colonial wars, from the 1870s to the 1930s. The book offers a new understanding of the mutually dependent interaction between indigenous peoples and colonial powers, and how collected remains became regarded as objects of wider significance.